THE RELATIONSHIP BETWEEN DURATION OF GAS EMISSION EXPOSURE AND DRY EYE SYNDROME (DES) ON TAXIBIKE DRIVERS IN CENTRAL JAKARTA: Oral Presentation - Observational Study - General practitioner - Muhammad Ferdiansyah; P. Rahmat Daeli; Alfoni Parsiska; Clarissa; M. Dwi Nugroho (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Dry eye syndrome (DES) is a breakdown in the natural layer of tears that coats the front of the eye. Air quality in Jakarta indicated to be harmful to human health. The average annual PM 2.5 figure in Central Jakarta recorded 27.6 μg/m3. This figure is far beyond WHO standard that is 10 μg/m3. According to AAO one of the risk factors for dry eyes is exposure/injury to chemicals and the environment (dusty, windy, hot/dry). Therefore duration of traffic related air pollutions exposure may have an effect with the severity of dry eye syndrome on taxibike drivers in Central Jakarta. Methods : Analytic observation with cross sectional approach. Population was 196 taxibike drivers of Central Jakarta from April-May 2023. Data collection was by means of a questionnaire containing identity,informed consent,duration of exposure,and DES questions accordance with OSDI provisions. The results obtained are then recorded, aggregated, and entered into charts and tables. Hypothesis test used is chi-square. Results : There were 196 participated in this study. A total of 8 participants(4,1%) with >12hours duration of exposure experienced severe dry eyes, 18 participants(9.2%) experienced moderate, 102 participants(52%) experienced mild dry eyes and the rest was normal(34.6%). According to this, prevalence of DES was more frequent in taxibike drivers who worked 6-12hours more than in <6hours of worked (OR: 1.764) and the severity increased with duration of exposure(p<0.05). Conclusion : The duration of gas emission exposure has significant correlation with the frequency and severity of DES on taxibike drivers in Central Jakarta.